Heat exchanger
By using paper-based materials such as Calcium chloride and magnesium chloride in the partition members and interval members of the heat exchanger, the problem of the humidity adsorption effect of existing heat exchangers weakened with time, and an efficient and long-lasting heat exchange effect is achieved.
Patent Information
- Application Number
- JP2019177057
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-09-27
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2039-09-27
AI Technical Summary
The existing heat exchanger using Calcium chloride as the humidity adsorbent reduces the humidity adsorption effect over time, resulting in a decrease in heat exchange efficiency.
Partition members and spacers are used, which are held by paper-based materials (mainly composed of cellulose fibers) and salt substances such as calcium chloride and magnesium chloride, and do not contain flame inhibitors. The partition members and spacers of the heat exchanger are uniformly distributed in the surface or fiber gap of the paper-based material to improve humidity conductivity and flame inhibition.
It extends the durability of the humidity adsorption effect, improves the heat exchange efficiency, and enables the heat exchanger to run efficiently for a longer period of time.
Smart Images

Figure 0007665281000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat exchanger, a base paper for a spacing member, and a manufacturing method for the base paper for the spacing member. More specifically, the present invention relates to a heat exchanger that exchanges both sensible heat (temperature) and latent heat (humidity) when supplying fresh outside air and discharging dirty air from inside a room, a base paper for a spacing member used in the heat exchanger, and a manufacturing method for the base paper for the spacing member. [Background technology]
[0002] 2. Description of the Related Art Conventionally, a heat exchanger that exchanges heat between intake air and exhaust air during ventilation has been used as a device capable of ventilating a room without impairing the effectiveness of cooling or heating. A widely used heat exchanger is one in which multiple partition members are stacked with spacing members between them, and the partition members separate an air supply path that introduces outside air into the room from an exhaust path that exhausts indoor air to the outside.
[0003] This partition material must have high moisture permeability in order to exchange sensible heat (temperature) and latent heat (humidity) at the same time while blocking the passage of air between the intake and exhaust air paths. For this reason, the partition material is made of a paper base material that holds a moisture absorbent. When the partition member holds a moisture absorbent, it easily absorbs moisture inside, allowing smooth movement of water vapor and improving moisture permeability.
[0004] In addition, since heat exchangers are required to be flame retardant, flame retardants are held in partition members and spacing members. Patent Document 1 discloses a heat exchanger in which a flame retardant is held in spacing members so that a large amount of moisture absorbent can be held in the partition members. Known moisture absorbents include water-soluble salts such as calcium chloride and lithium chloride, and water-insoluble or poorly water-soluble salts such as silica gel and zeolite. In particular, calcium chloride is considered to have excellent moisture absorption effect and is economical (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-147279 A [Patent Document 2] JP 2017-179613 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, in heat exchangers that use calcium chloride as a moisture absorbent, the moisture absorption effect decreases over time, and there are cases where efficient heat exchange cannot be performed. In view of the above circumstances, the present invention aims to provide a heat exchanger whose moisture absorption effect is not likely to decrease over time and which is capable of efficient heat exchange for a long period of time, a base paper for a spacing member used in this heat exchanger, and a method for manufacturing the base paper for the spacing member. [Means for solving the problem]
[0007] In order to achieve the above object, the present invention employs the following configuration. [1] A liquid supply system comprising: a plurality of partition members; and a plurality of spacing members that form flow paths between the partition members and maintain a spacing between the partition members; The plurality of partition members include a paper base material mainly composed of cellulose fiber, and one or more selected from the group consisting of calcium chloride, magnesium chloride, and lithium chloride held on the paper base material, and do not include any other flame retardant; A heat exchanger characterized in that the plurality of spacing members contain one or more members selected from the group consisting of a paper base material mainly composed of cellulose fiber and calcium chloride and magnesium chloride held on the paper base material, and do not contain any other flame retardants. [2] The heat exchanger described in [1], wherein the plurality of spacing members hold one or more types selected from the group consisting of calcium chloride and magnesium chloride on at least both surfaces of the paper base material. [3] The plurality of partition members have a density of 0.9 to 1.2 g / cm 3 The heat exchanger according to [1] or [2], [4] The flow path includes a first flow path and a second flow path formed in directions intersecting each other, The heat exchanger according to any one of [1] to [3], wherein the first flow path and the second flow path are adjacent to each other with the partition member interposed therebetween. [5] A heat exchanger including a plurality of partition members and a plurality of spacing members that form flow paths between the plurality of partition members and maintain the spacing between the partition members, the base paper for the spacing members being used as the spacing members, A base paper for spacing members, comprising a paper base material mainly composed of cellulose fibers and at least one selected from the group consisting of calcium chloride and magnesium chloride held on the paper base material, and containing no other flame retardants. [6] The base paper for spacing members according to [5], wherein at least one selected from the group consisting of calcium chloride and magnesium chloride is held on at least both surfaces of the paper base material. [7] A method for manufacturing a base paper for a spacer used in a heat exchanger including a plurality of partition members and a plurality of spacers that form flow paths between the partition members and maintain a space between the partition members, comprising: A method for manufacturing base paper for spacing members, characterized in that a paper base material mainly composed of cellulose fibers is coated or impregnated with a solution containing one or more types selected from the group consisting of calcium chloride and magnesium chloride, and containing no other flame retardants. [8] The amount of one or more selected from the group consisting of calcium chloride and magnesium chloride is 1 m 2 The method for producing a base paper for a spacer according to [7], further comprising applying or impregnating the base paper with the solution so that the amount of the solution is 3 to 15 g per sheet. Effect of the Invention
[0008] The heat exchanger of the present invention is resistant to deterioration of its moisture absorbing effect over time, and is capable of efficient heat exchange for a long period of time. The base paper for spacing members of the present invention can be used in the heat exchanger of the present invention, and the base paper for spacing members of the present invention can be manufactured according to the manufacturing method for the base paper for spacing members of the present invention. [Brief description of the drawings]
[0009] [Figure 1] 1 is a perspective view showing a heat exchanger according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Heat exchanger] 1 is a perspective view showing a heat exchanger 1 according to one embodiment of the present invention. The heat exchanger 1 is composed of a plurality of partition members 2 and a plurality of spacing members 3 that form flow paths between the plurality of partition members 2 and maintain the spacing between the partition members 2. The partition member 2 is configured as a flat plate having a square, diamond or other shape, and the spacing member 3 is formed as a corrugated plate having a sawtooth, sinusoidal or other wave shape whose projected planar shape matches the partition member 2. For example, it is formed by corrugating to have a shape similar to the core of cardboard. The ridges and valleys of the corrugated shape of the spacing member 3 are bonded to the partition member 2.
[0011] This spacing member 3 is adhered to the partition member 2 on one side with the partition member 2 sandwiched in between, with the direction of the wavy ridge line being the first direction I, and on the other side, it is adhered to the partition member 2 with the direction of the wavy ridge line being the second direction B. The bonding can be performed using a method that uses an adhesive or a thermal bonding method that does not use an adhesive, but a method that uses an adhesive is preferable because it can firmly bond the spacing member 3 and the partition member 2. As the adhesive, a known adhesive such as a polyvinyl alcohol adhesive or a polyvinyl acetate adhesive can be used. A moisture absorbent can be blended into the adhesive. Examples of moisture absorbents that can be blended include calcium chloride, magnesium chloride, and lithium chloride. The adhesive can also be blended with an anti-mold agent, a thickener, and the like. Spacing members 3 whose wavy ridge lines are oriented in a first direction I and spacing members 3 whose wavy ridge lines are oriented in a second direction B that intersects with the first direction I are adjacent to each other across a partition member 2 and stacked alternately.
[0012] A plurality of first flow paths 4 are formed along the first direction A between the spacing member 3 whose wavy ridge lines are oriented in the first direction A and the partition members 2 on both sides. A plurality of second flow paths 5 are formed along the second direction B between the spacing member 3 whose wavy ridge lines are oriented in the second direction B and the partition members 2 on both sides.
[0013] Spacing members 3 whose wavy ridge lines are oriented in a first direction I and spacing members 3 whose wavy ridge lines are oriented in a second direction B are stacked alternately with the partition member 2 sandwiched between them, so that the first flow path 4 and the second flow path 5 are also formed alternately along the thickness direction (the up-down direction in Figure 1). For example, the first flow path 4 is supplied with air, and the second flow path 5 is supplied with exhaust air, and heat exchange takes place between the supply air and the exhaust air via the partition member 2.
[0014] The crossing angle between the first direction A and the second direction B is set to 90 degrees or close to 90 degrees depending on the shape of the partition member 2. For example, if the partition member 2 is square, the crossing angle between the first direction A and the second direction B is preferably set to 90 degrees, and if the partition member 2 is rhombus, the crossing angle between the first direction A and the second direction B is preferably set to close to the angle at which lines connecting the midpoints of opposing sides of the partition member 2 intersect.
[0015] The average pitch of the corrugations of the spacing member 3 is preferably 1.5 to 8 mm, more preferably 2 to 7 mm, and even more preferably 4 to 6.5 mm. The average height of the corrugations of the spacing member 3 is preferably 1 to 5 mm, more preferably 1.3 to 4 mm, and even more preferably 1.5 to 3.5 mm. When the average pitch and average height of the corrugations of the spacing member 3 are equal to or greater than the preferred lower limit values, ventilation of the first flow path 4 and the second flow path 5 is easily ensured. When the average pitch and average height of the corrugations of the spacing member 3 are equal to or less than the preferred upper limit values, contact between the gas passing through the first flow path 4 and the second flow path 5 and the partition member 2 is easily ensured, and efficiency of heat exchange is easily ensured.
[0016] The heat exchanger 1 can be manufactured by alternately stacking partition member base paper and corrugated spacing member base paper with the corrugated ridge and valley portions of the spacing member base paper adhered to the partition member base paper on both sides, and then cutting to the specified shape. When stacking, spacing member base paper in which the direction of the wavy ridge line is the first direction (I) and spacing member base paper in which the direction of the wavy ridge line is the second direction (B) are alternately repeated with the partition member base paper sandwiched therebetween.
[0017] [Partition material base paper] The partition member 2 contains a paper base material mainly composed of cellulose fibers and at least one selected from the group consisting of calcium chloride, magnesium chloride and lithium chloride held on the paper base material, and does not contain any other flame retardant. Therefore, the base paper for partition member that constitutes the partition member 2 also contains a paper base material whose main component is cellulose fiber and one or more types selected from the group consisting of calcium chloride, magnesium chloride, and lithium chloride held on the paper base material, and does not contain any other flame retardants.
[0018] The paper base material is composed mainly of cellulose fibers. "Composed mainly of" means that the ratio of the cellulose fibers to the entire paper base material is 50% by mass or more. The paper base material is typically composed of pulp containing cellulose fibers. Examples of pulp containing cellulose fibers include wood pulp and non-wood pulp. Examples of wood pulp include softwood pulp and hardwood pulp. Examples of non-wood pulp include hemp pulp, kenaf pulp, bamboo pulp, etc. The wood pulp may be one that has been subjected to a cooking step and / or a bleaching step. Generally, wood pulp is used after being subjected to various cooking steps and bleaching steps in order to remove components other than cellulose from the raw wood material. In the present invention, the cooking step and bleaching step are not particularly limited, and any known method can be used as appropriate. As the pulp, softwood pulp is preferred, and softwood kraft pulp (NBKP) is more preferred, since it can improve the strength of the base paper and the CO2 barrier property. These pulps may be used alone or in combination of two or more.
[0019] The paper substrate may further contain other fibers besides cellulose fibers, such as synthetic fibers such as rayon fibers, polyethylene fibers, polypropylene fibers, and polyester fibers. The paper base material may contain internal additives such as sizing agents, paper strength agents, colorants, etc. As the internal additives, known ones can be used.
[0020] Since calcium chloride, magnesium chloride, and lithium chloride all function as moisture absorbents, by retaining one or more of these, the moisture permeability of the partition member 2 is improved. Furthermore, since calcium chloride and magnesium chloride have flame retardant properties, when one or more of these are held, the flame retardant properties of the partition member 2 are improved.
[0021] The distribution state of calcium chloride, magnesium chloride and lithium chloride in the base paper for the partition member is not particularly limited, but it is preferable that some or all of them are retained on at least both surfaces of the paper base material, as this makes it easier to efficiently improve the moisture permeability of the partition member 2. Being held on the surface of the paper substrate may mean a state in which the material is attached to the surface of the paper substrate, or a state in which the material has entered into gaps between fibers near the surface of the paper substrate, or may include both a state in which the material is attached to the surface of the paper substrate and a state in which the material has entered into gaps between fibers near the surface of the paper substrate.
[0022] When some or all of the calcium chloride, magnesium chloride, and lithium chloride in the partition member base paper are retained in the gaps between the fibers of the paper base material, the concentration in the thickness direction of the paper base material may be uniform, or may have a concentration gradient in which the concentration decreases from the surface of the paper base material toward the inside. From the viewpoint of easily and efficiently improving the moisture permeability of the partition member 2, it is preferable that the concentration gradient in which the concentration decreases from the surface of the paper base material toward the inside.
[0023] The amount of one or more selected from the group consisting of calcium chloride, magnesium chloride, and lithium chloride is, in anhydrous terms, 1 m 2 The amount is preferably 2 to 15 g, and more preferably 3 to 10 g per unit weight, and more preferably 5 to 30% by weight, and more preferably 10 to 25% by weight, calculated as anhydrous, based on the total weight of the partition member base paper. In particular, when calcium chloride is retained, its content is preferably 5 to 30 mass % in anhydrous equivalent, more preferably 10 to 20 mass %, based on the total mass of the partition member base paper. When the calcium chloride content is equal to or higher than the lower limit of the above range, moisture absorption and release performance and flame retardancy are more excellent. When the calcium chloride content is equal to or lower than the upper limit of the above range, dripping due to excess moisture at high humidity is unlikely to occur.
[0024] Examples of flame retardants that should not be contained in the partition member base paper include ammonium salt-based flame retardants such as diammonium phosphate, ammonium chloride, and ammonium sulfate. By not including these components, the moisture absorption effect of calcium chloride, etc. is less likely to decrease over time, enabling efficient heat exchange over a long period of time. When these components are included, the moisture absorption effect of calcium chloride, etc. decreases over time, presumably because calcium chloride, etc. reacts with these components to form complexes.
[0025] The partition member base paper may contain a humidity control agent, which makes it difficult for condensation to occur. The temperature adjusting agent preferably contains a latent heat storage component. The latent heat storage component has the property of absorbing (storing) heat when it changes phase (melts) from a solid state to a liquid state, and dissipating heat when it changes phase (solidifies) from a liquid state to a solid state. Due to this property, when the temperature around the temperature adjusting agent changes from a temperature lower than the melting point (or freezing point) of the latent heat storage component to a temperature higher than that, or from a temperature higher than the melting point (or freezing point) to a temperature lower than that, heat absorption or dissipation occurs at a temperature near the melting point (or freezing point) of the latent heat storage component, and the temperature is maintained constant.
[0026] The melting point of the latent heat storage component is preferably 10 to 35° C., and more preferably 20 to 35° C. If the melting point of the latent heat storage component is within the above range, condensation is unlikely to occur on the surface of the partition member 2 when heat is exchanged between indoor air and outdoor air via the partition member 2, even if there is a large temperature difference between the air. Specific examples of the latent heat storage component and the manner of retention are similar to those described in Patent Document 2.
[0027] The partition member base paper may further contain other additives as necessary within the scope of not impairing the effects of the present invention. Examples of other additives include mildewproofing agents and polymer compounds. Other additives may be contained in the partition member base paper in a state where they are adhered to the surface of the paper substrate, or they may be contained in the partition member base paper in a state where they have penetrated into the gaps between the fibers of the paper substrate, or they may be contained in the partition member base paper in both a state where they are adhered to the surface of the paper substrate and a state where they have penetrated into the gaps between the fibers of the paper substrate.
[0028] The base paper for partition members may have a coating layer containing a polymer resin on one or both sides of the paper substrate in order to improve the gas barrier properties. Examples of the polymer resin used for such a purpose include polyvinyl alcohol (PVA). The coating layer is formed by applying a coating liquid containing a polymer resin to a paper substrate and drying it. Since the paper substrate is porous, the coating layer is usually present at least partially in the gaps between the fibers below the surface of the paper substrate. A part of the coating layer may be present on the surface of the paper substrate.
[0029] The density of the base paper for partition members is 0.9 to 1.2 g / cm 3 and preferably 0.95 to 1.15 g / cm 3 More preferably, it is 1.0 to 1.1 g / cm 3 It is even more preferable that: By making the density of the partition member base paper equal to or greater than the lower limit of the preferred values, the gas barrier properties are improved and the thickness can be reduced, thereby increasing the thermal conductivity and improving the heat exchange efficiency. By making the density of the partition member base paper equal to or less than the upper limit of the preferred values, the gaps between the fibers can maintain an appropriate water retention. The density of the base paper for partition members is calculated from the measured values of thickness and basis weight in accordance with JIS P 8118 (1998).
[0030] The moisture permeability of the base paper for partition materials is 1,000g / (m 2 24h) or more is preferable, and 1,200 (m 2 24h) or more is preferable, and 1,500 (m 2 It is even more preferable that the time is 24 hours or more. When the moisture permeability of the partition member base paper is equal to or higher than the lower limit, the efficiency of latent heat (humidity) exchange between the intake air and the exhaust air is excellent. The moisture permeability of the partition member base paper is calculated from the mass increment C per hour calculated by the following formula (1) when the moisture permeability test is performed in accordance with JIS Z 0208 (1976) except that the temperature and humidity conditions are changed to 20°C and 65% relative humidity (RH), and the mass increment (g) one hour after the start of the test is defined as A and the mass increment (g) from one hour to two hours after the start of the test is defined as B. Specifically, the mass increment C per hour is multiplied by 24 to obtain the value per 24 hours (g / 24h), and this value is multiplied by the area (m2) of the partition member base paper. 2 ) to obtain the moisture permeability (g / (m 2 24h) is required. Mass increment per hour C = (A + B) / 2 (1)
[0031] The air permeability of the partition member base paper is preferably 1,000 seconds or more, and more preferably 7,000 seconds or more. When the air permeability of the partition member base paper is equal to or more than the lower limit, mixing of the supply air and the exhaust air can be sufficiently suppressed. The air permeability of the base paper for partition members is measured in accordance with the Oken air permeability method of JAPAN TAPPI Paper and Pulp Testing Method No. 5-2:2000.
[0032] The basis weight of the base paper for partition members is 20 to 80 g / m 2 It is preferable that the thickness is 30 to 60 g / m 2 It is more preferable that the base paper for partition member has a basis weight of not less than the lower limit of the above range, and thus has excellent mechanical strength and gas barrier properties. If the basis weight of the base paper for partition member is not more than the upper limit of the above range, the base paper for partition member has excellent heat conductivity, and the weight of the partition member 2 formed from the base paper for partition member is reduced, and the number of stacked layers of the partition member 2 in the heat exchanger can be increased, and the heat exchange efficiency can be further improved. The basis weight of the partition member base paper is measured in accordance with JIS P 8124 (2011). The basis weight of the paper base material can also be determined in the same manner.
[0033] The thickness of the partition member base paper is preferably 0.01 to 0.1 mm, and more preferably 0.03 to 0.05 mm. When the thickness of the partition member base paper is equal to or greater than the lower limit of the above range, the mechanical strength and gas barrier properties are excellent. When the thickness of the partition member base paper is equal to or less than the upper limit of the above range, the heat transfer properties are excellent, and the partition member 2 formed from the partition member base paper is lighter, allowing the number of stacked layers of the partition member 2 in the heat exchanger to be increased, thereby further improving the heat exchange efficiency. The thickness of the base paper for the partition member is measured in accordance with JIS P 8118 (2014). The thickness of the paper substrate can also be determined in the same manner.
[0034] [Manufacturing method of base paper for partition material] The base paper for partition members can be produced by coating or impregnating a paper base material with a solution (hereinafter sometimes referred to as "solution for partition members") that contains one or more selected from the group consisting of calcium chloride, magnesium chloride, and lithium chloride and does not contain any other flame retardants. The solution may further contain a moisture conditioner or other additives, if necessary.
[0035] The paper base material can be produced by papermaking a papermaking raw material containing cellulose fibers. The papermaking raw material may contain other fibers and internal additives as necessary. The papermaking of the raw material for papermaking can be carried out by using any known method.
[0036] When the cellulose fibers are pulp, the pulp is beaten according to the type of paper to be used and then subjected to the papermaking process. The beating of the pulp can be carried out by a known method, and for example, a beating device such as a double disc refiner (DDR) is preferably used. Generally, when the pulp is beaten, the pulp fibers become more flexible, and it becomes easier to obtain a high-density paper base material. The densification of the paper base material improves the gas barrier property. Therefore, it is preferable that the pulp used in the manufacture of the paper base material is beaten. On the other hand, when the pulp is beaten, the drainage becomes poor and the operating efficiency decreases. Therefore, the degree to which the pulp is beaten (the degree of beating) is appropriately selected in consideration of the strength, gas barrier property, basis weight, operating efficiency, etc. of the target paper base material.
[0037] The degree of beating of the pulp is preferably 100 to 600 mL, more preferably 150 to 500 mL, as the irregular freeness described below. When the irregular freeness is equal to or less than the upper limit of the above range, the retention of calcium chloride and the like and the gas barrier properties are more excellent. When the irregular freeness is equal to or more than the lower limit of the above range, the operating efficiency is good.
[0038] Irregular freeness: Irregular freeness is a measurement method based on JIS P 8121-2 (2012) "Pulp - Freeness test method - Part 2: Canadian standard freeness method", but the amount of pulp used is equivalent to 0.3 g in bone dry weight, and the perforated sieve plate attached to the Canadian standard freeness tester is an 80 mesh sieve plate made of stainless wire. Specifically, the disintegrated pulp was diluted with water to a solid concentration of 0.030 mass%. The sample temperature was adjusted to 20°C, and 1000 mL of the sample was transferred to a graduated cylinder. The opening of the graduated cylinder was blocked by hand, the graduated cylinder was inverted, the sample was mixed, and the sample was poured into the filter bottle. The bottom lid was opened, and after 5 seconds, the air cock was opened to allow the sample to flow down. The wastewater from the side orifice was collected, the amount was read, and the amount read was taken as the irregular freeness value.
[0039] The paper substrate may be a paper obtained by making paper from a papermaking raw material. If necessary, the paper after making may be subjected to parchment treatment to form the paper substrate. By performing parchment treatment, the effect of improving paper strength and gas barrier properties can be obtained. Parchment treatment is a treatment in which sulfuric acid is used as a cellulose swelling agent to modify the cellulose. Parchment treatment can be performed by a conventional method.
[0040] The application or impregnation of the partition member solution can be carried out by a known method. For example, after the papermaking raw material is made and dried in a papermaking machine, the solution for the partition member is applied to the paper base material in-line using a coating device (size press, gate roll coater, rod coater, blade coater, etc.) in the papermaking machine, and then dried to obtain a base paper for the partition member. Alternatively, after the paper base material is made and dried, the solution for the partition member can be applied or impregnated to the paper base material offline using a coating device or impregnation device provided separately from the papermaking machine, and then dried to obtain a base paper for the partition member. Alternatively, after the paper base material is made and dried, parchment treatment is performed, and then the solution for the partition member is applied or impregnated, and then dried to obtain a base paper for the partition member.
[0041] The application or impregnation of the partition member solution is performed by setting various conditions such as the paper base material used, the composition of the partition member solution, the amount of the partition member solution applied, and post-processing so that the content of one or more selected from the group consisting of calcium chloride, magnesium chloride, and lithium chloride in the resulting partition member base paper, the density of the partition member base paper, etc., are each within the above-mentioned preferred ranges.
[0042] In addition, calcium chloride and the like are highly hygroscopic and usually retain water of crystallization, making it difficult to calculate the content based on the dry mass. Therefore, when producing a base paper for a partition member by the above-mentioned production method, it is preferable to calculate the content of one or more selected from the group consisting of calcium chloride, magnesium chloride, and lithium chloride as a value obtained by multiplying the wet adhesion amount of the partition member solution by the concentration of calcium chloride and the like as an anhydride. The concentration of calcium chloride and the like (anhydride) in the partition member solution can be determined by EDTA (ethylenediaminetetraacetic acid) titration method.
[0043] After the partition member solution is applied and dried, the obtained partition member base paper may be subjected to a calendaring treatment. By performing the calendaring treatment, the density of the partition member base paper is increased and the thickness is reduced. By increasing the density of the partition member base paper, the gas barrier properties are improved, and by reducing the thickness of the partition member base paper, the thermal conductivity is improved, resulting in improved heat exchange efficiency. The calendering equipment used for the calendering is not particularly limited, and known calendering equipment such as a machine calender, a soft nip calender, a super calender, and a gloss calender can be appropriately used.
[0044] After applying and drying the solution for the partition member, or after applying, drying and calendaring the solution for the partition member, a coating liquid containing a polymer resin such as polyvinyl alcohol (PVA) may be applied to one or both sides of the paper substrate and dried to form a coating layer containing a polymer resin, for the purpose of improving gas barrier properties, etc.
[0045] [Base paper for spacing components] The spacing member 3 contains a paper base material mainly composed of cellulose fibers and at least one selected from the group consisting of calcium chloride and magnesium chloride held on the paper base material, and does not contain any other flame retardant. Therefore, the base paper for the spacing member that constitutes the spacing member 3 also contains a paper base material whose main component is cellulose fiber and one or more types selected from the group consisting of calcium chloride and magnesium chloride retained on the paper base material, and does not contain any other flame retardants.
[0046] The paper base material is composed mainly of cellulose fibers. "Composed mainly of" means that the proportion of cellulose fibers in the entire paper base material is 50% by mass or more. The paper base material is typically composed of pulp containing cellulose fibers. Examples of pulp containing cellulose fibers include the same pulps as those listed in the description of the base paper for partition members. Similarly, the pulp may be one that has been subjected to a cooking process and / or a bleaching process. As the pulp, from the viewpoint of base paper strength, kraft pulp is preferred, bleached kraft pulp is more preferred, and among these, bleached kraft pulp of softwood is preferred. These pulps may be used alone or in combination of two or more.
[0047] The paper substrate may further contain other fibers besides cellulose fibers, such as synthetic fibers such as rayon fibers, polyethylene fibers, polypropylene fibers, and polyester fibers. The paper base material may contain chemicals such as sizing agents, paper strength agents, colorants, etc. As the internally added chemicals, known chemicals can be used.
[0048] Since calcium chloride and magnesium chloride both have flame retardant properties, the flame retardant properties of the spacing member 3 are improved by containing at least one of these. In addition, calcium chloride and magnesium chloride also function as moisture absorbents, so by retaining one or more of these, moisture can be temporarily absorbed not only by the partition member 2 but also by the spacing member 3. This makes it possible to suppress dripping, which is likely to occur during heat exchange at high humidity.
[0049] The distribution state of calcium chloride and magnesium chloride in the base paper for the spacing member is not particularly limited, but in order to allow the spacing member 3 to efficiently absorb moisture, it is preferable that some or all of them are retained on at least both surfaces of the paper base material, as with the base paper for the partition member.
[0050] When some or all of the calcium chloride and magnesium chloride in the base paper for the spacing member are retained in the gaps between the fibers of the paper base material, the concentration in the thickness direction of the paper base material may be uniform, or may have a concentration gradient in which the concentration decreases from the surface of the paper base material toward the inside. From the viewpoint of making it easier for the spacing member 3 to efficiently absorb moisture, it is preferable for the concentration to be a concentration gradient in which the concentration decreases from the surface of the paper base material toward the inside.
[0051] The amount of one or more selected from the group consisting of calcium chloride and magnesium chloride is, in anhydrous terms, per 1 m of base paper for spacing members. 2 The weight is preferably 3 to 15 g, and more preferably 3 to 11 g per unit weight of the base paper for the spacing member. The weight is preferably 4 to 25% by weight, and more preferably 6 to 16% by weight, calculated as anhydrous, based on the total weight of the base paper for the spacing member. In particular, when calcium chloride is contained, its content is preferably 4 to 30 mass % in anhydrous equivalent, more preferably 6 to 16 mass %, based on the total mass of the base paper for the spacer. When the calcium chloride content is equal to or higher than the lower limit of the above range, the flame retardancy and moisture absorption and release performance are more excellent. When the calcium chloride content is equal to or lower than the upper limit of the above range, dripping due to excess moisture at high humidity is unlikely to occur.
[0052] The flame retardants that should not be contained in the base paper for the spacer are the same as those listed as the flame retardants that should not be contained in the base paper for the partition member. By not including these components, the moisture absorption effect of calcium chloride, etc. in the partition member 2 is less likely to decrease over time, enabling efficient heat exchange over a long period of time. When the spacer base paper contains these components, the moisture absorption effect of calcium chloride, etc. in the partition member 2 decreases because the calcium chloride, etc. in the partition member 2 reacts with these components contained in the spacer 3 over time to form a complex.
[0053] The base paper for the spacer may contain a humidity control agent, similar to the base paper for the partition member. By containing a temperature control agent, the heat exchange efficiency is improved. The base paper for the spacer may further contain other additives as necessary within the range that does not impair the effects of the present invention. Examples of other additives include mildewproofing agents and polymer compounds. Other additives may be included in the base paper for the spacing member in a state where they are adhered to the surface of the paper base material, or they may be included in the base paper for the spacing member in a state where they have penetrated into the gaps between the fibers of the paper base material, or they may be included in the base paper for the spacing member in both a state where they are adhered to the surface of the paper base material and a state where they have penetrated into the gaps between the fibers of the paper base material.
[0054] The density of the base paper for the spacer is 0.5 to 1.2 g / cm 3 and preferably 0.7 to 1.1 g / cm 3 More preferably, it is 0.73 to 0.95 g / cm 3 It is even more preferable that: When the density of the spacer base paper is equal to or greater than the lower limit of the preferred values, the spacer base paper has excellent processability, and when the density of the spacer base paper is equal to or less than the upper limit of the preferred values, the spacer base paper has excellent water retention. The density of the base paper for the spacer is calculated from the measured values of thickness and basis weight in accordance with JIS P 8118 (1998).
[0055] The basis weight of the base paper for the spacing members is 30 to 200 g / m 2 It is preferable that the thickness is 50 to 100 g / m 2 When the basis weight of the spacer base paper is equal to or more than the lower limit of the above range, the mechanical strength is excellent. When the basis weight of the spacer base paper is equal to or less than the upper limit of the above range, the cost efficiency and processability are excellent. The basis weight of the base paper for the spacer is measured in accordance with JIS P P8124 (2011). The basis weight of the paper base material can also be determined in the same manner.
[0056] The thickness of the spacing member base paper is preferably 0.01 to 0.2 mm, and more preferably 0.07 to 0.15 mm. When the thickness of the spacing member base paper is equal to or greater than the lower limit of the above range, the mechanical strength is excellent. When the thickness of the spacing member base paper is equal to or less than the upper limit of the above range, the cost efficiency and processability are excellent. The thickness of the base paper for the spacer is measured in accordance with JIS P P8118 (2014). The thickness of the paper substrate can also be determined in the same manner.
[0057] [Manufacturing method of base paper for spacer components] The base paper for spacing members can be produced by coating or impregnating a paper base material with a solution (hereinafter sometimes referred to as "spacing member solution") that contains one or more types selected from the group consisting of calcium chloride and magnesium chloride and does not contain any other flame retardants. The solution preferably contains a penetration promoter that promotes the penetration of calcium chloride or magnesium chloride into the paper substrate. Examples of the penetration promoter include volatile solvents such as alcohols. If necessary, the solution may further contain a moisture conditioner, a preservative, an anti-mold agent, a deodorizer, a fragrance, or other additives.
[0058] The paper base material can be produced by papermaking a papermaking raw material containing cellulose fibers. The paper base material may be a single-ply paper or a multi-ply paper. The papermaking raw material may contain other fibers and internal additives as necessary. The papermaking of the raw material for papermaking can be carried out by using any known method.
[0059] When the cellulose fibers are pulp, the pulp is subjected to a beating treatment depending on the type of paper to be used and then subjected to a papermaking process. The beating treatment of the pulp can be carried out by a known method, as explained in the method for producing the base paper for partition members, and for example, a beating device such as a double disc refiner (DDR) is preferably used.
[0060] The degree of beating of the pulp when producing the base paper for the spacing member is preferably 100 to 700 mL, more preferably 530 to 700 mL, in terms of freeness (so-called freeness) according to JIS P 8121-2 (Canadian Standard Freeness Method). By keeping the freeness within the above range, sufficient paper strength as a spacing member can be obtained. The paper substrate may be paper obtained by making papermaking raw materials as it is, or may be subjected to a calendar treatment as necessary.
[0061] The coating or impregnation of the spacing member solution can be carried out by a known method, similar to that described for the manufacturing method of the partition member base paper. After making and drying the paper base material, the spacing member solution can be coated and dried to obtain the spacing member base paper.
[0062] When applying or impregnating the spacing member solution, various conditions such as the paper base material used, the composition of the spacing member solution, the amount of spacing member solution applied, and post-processing are set so that the content of one or more selected from the group consisting of calcium chloride and magnesium chloride in the resulting spacing member base paper, the density of the spacing member base paper, etc. are each within the preferred ranges described above. When the base paper for partition members is manufactured by the above-mentioned manufacturing method, the content of one or more selected from the group consisting of calcium chloride and magnesium chloride can be determined in the same manner as described in the description of the manufacturing method for the base paper for partition members.
[0063] After the application of the spacing member solution and drying, the obtained spacing member base paper may be subjected to a calendaring treatment. By performing the calendaring treatment, the density of the spacing member base paper is increased and the thickness is reduced. By reducing the thickness of the spacing member base paper, the effect of reducing pressure loss is obtained. As explained in the description of the method for producing the partition member base paper, the calendering equipment used in the calendering is not particularly limited. [Explanation of symbols]
[0064] 1... heat exchanger, 2... partition member, 3... spacing member, 4... first flow path, 5... second flow path, A...first direction, B...second direction.
Claims
1. A heat exchanger that performs heat exchange of both sensible heat and latent heat, a plurality of partition members; and a plurality of spacing members that form flow paths between the plurality of partition members and maintain spacing between the partition members; the plurality of partition members are made of a partition member base paper containing a paper base material mainly composed of cellulose fiber and calcium chloride held in the paper base material, and containing no flame retardant other than calcium chloride; the amount of calcium chloride held in the partition member base paper is 5 to 30% by mass, calculated as an anhydrous amount, based on the total mass of the partition member base paper; the plurality of spacing members are made of a spacing member base paper that includes a paper base material mainly composed of cellulose fiber and one or more selected from the group consisting of calcium chloride and magnesium chloride held on the paper base material, and does not include any flame retardant other than calcium chloride and magnesium chloride; The amount of one or more selected from the group consisting of calcium chloride and magnesium chloride held in the base paper for spacing members is, in terms of anhydrous, 2 The heat exchanger according to claim 1, wherein the weight of the heat exchanger is 3 to 15 g per unit area.
2. The heat exchanger according to claim 1 , wherein the plurality of spacing members hold at least one selected from the group consisting of calcium chloride and magnesium chloride on at least both surfaces of the paper base material.
3. The plurality of partition members have a density of 0.9 to 1.2 g / cm 3 The heat exchanger according to claim 1 or 2,
4. The flow path includes a first flow path and a second flow path formed in directions intersecting each other, 4. The heat exchanger according to claim 1, wherein the first flow path and the second flow path are adjacent to each other with the partition member interposed therebetween.
Citation Information
Patent Citations
Heat exchanger and heat exchanging ventilator
JP2007147279A
Moisture permeable sheet, manufacturing method therefor, base paper for all heat exchanger element, and all heat exchanger element
JP2017179613A
Sensible heat heat-transfer element
JP2019158274A
Total heat exchanger element and process for manufacturing the same
WO2009004695A1
Base sheet for total heat exchanger element
WO2019151211A1